Junction Temperature Estimation of Direct-Drive GaN HEMTs in Two-Level Inverters for Driving PMSM Through Power Loss Analysis - Lee, In Ho; Park, Seong Mi; Cho, Young Hoon; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2024)
This paper presents junction temperature estimation method of direct-drive Gallium Nitride (GaN) high electron mobility transistors (HEMTs) in two-level inverters for driving permanent magnet synchronous motor (PMSM). GaN HEMTs exhibit high mobility of electrons due to two-dimensional electron gas (2DEG) formed between GaN layer and AlGaN layer. GaN HEMT is a positive polarity device which has a normally-on characteristic where the switch remains in on-state even in the absence of applied gate voltage. The implementation of normally-off characteristic is necessary to apply GaN HEMTs in power conversion system (PCS). Power losses of GaN HEMTs are generated during the operation of the PCS, which are transformed into thermal energy. The electrical property such as on-resistance, switching energy, and V-I characteristic varies with the junction temperature of GaN HEMTs. Therefore, variation of electrical properties should be considered in power loss profile. An RC Cauer network is utilized to model the thermal behavior. The power losses are converted into junction temperature using the characteristics of materials both internal and external to the GaN HEMTs. The validity of junction temperature estimation method is verified by simulation and experimental results.
Keywords: Direct drive; Estimation methods; Gallium nitride high electron mobility transistor; High electron-mobility transistors; Junction temperatures; Permanent Magnet Synchronous Motor; Powerloss; RC cauer network; Temperature estimation; Two-level inverters; GaN HEMT; Junction temperature; PMSM; Power loss; RC Cauer network; Two-level inverter